Analysis of correlations between indices of academic performance - Čikun, Jelena; Daunoravičius, Jonas-Vytautas; Radavičius, Marijus (Lietuvos matematikos rinkinys, 2023)
The paper is devoted to multivariate statistical analysis of academic performance data. The phenomina of general grade inflation and the effect of the first passing of an egzam on grades of the egzam are investigated by making use of general linear (mixed) model and logistic regresion.